Anaplastic large cell lymphoma masquerading as osteomyelitis of the shoulder: an uncommon presentation. (21st December 2016) - Tuck, Matthew; Lim, Jane; Lucar, Jose; Benator, Debra
Abstract : The presentation of anaplastic lymphoma kinase protein (ALK)-negative anaplastic large cell lymphoma (ALCL) in bone is rare. We describe a patient with ALK-negative ALCL presenting with clinical and radiographic findings suggesting osteomyelitis 6 months after left rotator cuff repair surgery. A review of the characteristics of ALK-negative ALCL with primary bone involvement is presented. ALCL should be considered in patients not responding to therapies for osteomyelitis.